The Utilization of Sexual and Reproductive Health Services Among Young Males in Indonesia: Does Their Knowledge of Reproductive Health Matter? - Desy Nuri Fajarningtiyas (Universitas Aisyah Pringsewu, 2022)
Ensuring the availability of sexual and reproductive health services for adolescents is essential to provide accurate sexual and reproductive health-related information in order to decrease the prevalence of early marriage and premarital sex as well as its outcomes. This study aims to examine the association of reproductive health knowledge and other factors among young males in Indonesia with the use of sexual and reproductive health services. The unit analysis used was 12,612 never-married men aged 15–24. Among respondents, 45% of them had poor knowledge of reproductive health, and 90.4% respondents used the services poorly. Using binomial logistic regression, this study finds that those who had good knowledge of reproductive health, were from a younger age group, had higher education level, were exposed to newspapers, magazines, and the internet, and had a discussion about reproductive health utilized the services better than their counterparts. Providing adolescent-friendly services with both providers and comfortable places in schools, primary health care, and community-based services and also increasing the involvement of teachers, health providers, and religious or community leaders in the services are expected to make the services more accessible for young males and raise their awareness about sexual and reproductive health matters. Abstrak: Memastikan ketersediaan layanan kesehatan seksual dan reproduksi bagi remaja sangat penting untuk menjamin ketersediaan informasi terkait kesehatan seksual dan reproduksi yang akurat, sehingga prevalensi pernikahan dini dan seks pranikah beserta konsekuensinya, dapat diturunkan. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan kesehatan reproduksi dan factor-faktor lainnya pada remaja laki-laki di Indonesia dengan pemanfaatan pelayanan kesehatan reproduksi dan seksual. Unit analisis yang digunakan dalam penelitian ini adalah 12.612 remaja pria belum menikah, berumur 15-24 tahun. Analisis deskriptif menunjukkan bahwa 45% responden masih memiliki pengetahuan kesehatan reproduksi yang rendah, dan sebanyak 90.4% responden masih belum memanfaatkan layanan kesehatan seksual dan reproduksi secara baik. Dengan menggunakan regresi logistik binomial, hasil penelitian ini menunjukkan bahwa remaja pria yang memiliki pengetahuan kesehatan reproduksi baik, berasal dari kelompok usia yang lebih muda, memiliki tingkat pendidikan yang tinggi, terpapar koran, majalah, dan internet, dan berdiskusi tentang kesehatan reproduksi cenderung memanfaatkan layanan dengan lebih baik. Menyediakan pelayanan kesehatan seksual dan reproduksi yang ramah remaja dengan tenaga kesehatan dan tempat yang nyaman di sekolah, Puskesmas, dan layanan berbasis masyarakat lainnya serta meningkatkan keterlibatan guru, tenaga kesehatan, dan tokoh agama atau tokoh masyarakat dalam pelayanan diharapkan menjadikan pusat pelayanan kesehatan seksual dan reproduksi lebih mudah diakses.